Five Years Study of Recurrent Febrile Seizure Risk Factors - Ausi Indriani; Nelly Amalia Risan; Titing Nurhayati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Nearly one-third of febrile seizure patients suffered recurrent febrile seizures. Several risk factors contribute to this recurrence, namely young age, family history of febrile seizures, low body temperature and rapid duration of fever before onset of seizures. Recently, the types of seizure and gender have been stated increasing risk of this recurrence. The objectives of this study was to identify the risk factors of recurrent febrile seizures.Methods: A descriptive study was carried out by retrieving data from inpatient medical records during the period of January 1st, 2009 to December 31st, 2013 at one of the top referral hospitals in West Java, Indonesia. Variables of this study were the first febrile seizure age, gender, type of febrile seizure, a family history of febrile seizure, a family history of epilepsy, body temperature when febrile seizure occurred and duration of fever before onset of seizure. The collected data were tabulated by frequency and percentage and displayed in tables.Results: Out of 154 patients with febrile seizures 58 suffered recurrent febrile seizures. Forty three percent had a first febrile seizure at the age of under12 months, 72% were male, 46% had fever less than 24 hours before the onset of seizure, 65% had complex febrile seizures, 28% had positive family history of febrile seizures, and 5% had positive family history of epilepsy. Conclusions: The risk factors for recurrent febrile seizures are young age, male, rapid duration of fever before onset of seizure and complex febrile seizure. DOI: 10.15850/amj.v4n2.1086